(3GdJQLeGf GdoeYQH Yf Ohd GdeTQb hGdeZQHs - (3CHhGdbGSe Hf CMeOHf Ydj Hf EHQGgje GdRjGfjs
(3ChdgG (B:s
(3JHOC aj CKfGA GdHGH GdKGef aj OhdI GdjhfGf HCQV GdQhe hZdHJge Ydi GdOhd s
(3BNQgG (B:s
(3HfgGjI GdcJGH s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B172s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B879 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B106 s
Keywords: (3GdJGQjNs